Fonološka zmožnost bosansko govorečih priseljenk in priseljencev: Jana Lovrec Srša, Gjoko Nikolovski (Stanje in perspektive uporabe govornih virov v raziskavah govora, 2024)
Phonological Competence of Bosnian-Speaking Immigrants. Of all the linguistic levels addressed in the teaching of one language as a second and foreign language, the phonetic-phonological level is the least represented. This is because communication is possible even when the pronunciation is not completely correct. The use of a communicative approach in foreign language teaching also affects the "neglect" of the phonetic-phonological level, as both students and teachers are aware that communication is possible despite incorrect/inadequate pronunciation. The paper deals with the phonological ability of non-Slovenian-speaking immigrants from Bosnia and Herzegovina who live in Maribor and learn Slovene as a second and foreign language (SSFL) to successfully integrate into the Slovenian environment. For this paper, a corpus of their spoken texts is analysed, in which the phonetic difficulties they face in learning SSFL are discussed and defined. The analysis is based on recordings of their spoken texts and registers the following problems: pronunciation of the semivowel, pronunciation of the v- before the (un)voiced consonant, pronunciation of the final -v after the vowel or r, pronunciation of the preposition v, pronunciation of the morphemic -ol- for the formerly voiced consonant in front of the consonant, pronunciation of the final -l after the vowel, pronunciation etc.